MAIN LEGAL PRINCIPLES OF ADMINISTRATIVE COURT PROCEDURAL LAW - Blegur, Spyendik Bernadus (Jurnal Hukum Peratun, 2022)
Three decades since the promulgation of Law no. 5 of 1986 concerning Administrative Court, developments in the procedural law of administrative courts are numerous and occur rapidly. However, with the rapid and many developments, there are still misunderstandings about the main principles of procedural law that apply in administrative courts. Therefore, this paper tries to re-explain the principles of procedural law in administrative courts. The writing method used in this research is a legal-normative approach using a statutory approach and a conceptual approach. This paper uses the legal-normative method, namely an approach based on legal materials by examining concepts, theories, legal principles and legislation, as well as literature related to the paper. It is found in this paper that the main legal principles in administrative court can be grouped into two, namely the principles related to formality and the principles related to the settlement of the dispute.